SELF-HARM RISK IN PREGNANT WOMEN WITH PERSONALITY DISORDER - Galih Puspita Citra Mahardhika (Journal of Psychiatry Psychology and Behavioral Research, 2023)
Background: Mental distress in being pregnant is still underreported due to the similarity with changes in pregnancy itself. Almost of women with personality disorder history report mental distress which induces suicide targets on attempted self-murder during pregnancy.Objective: To reveal the threat elements for self-harm behavior in a pregnant woman with a history of personality disorder.Methods: This paper included searching for pregnant women with a history of personality disorders, records of miscarriage, cigarette use, maternal dysfunction, adolescents, and depression during pregnancy who are at risk of committing suicide attempts or self-harm.Results: Self-harm risk in pregnant women involving adverse results not only suicide but also homicide. Self-harm can be triggered bysymptoms of depression before and after birth, economic state, social support, childhood physical and sexual experiences, mental state condition, education level, maturation of age, and social communication. Intervention needs to be assessed as soon as possible to refer to a psychiatrist and conduct Consultation liaison psychiatry as needed if found many comorbidities can disturb pregnant development.Conclusion: Self-harm in pregnant women with personality disorder had various risk factors not only from their personality disorder itself but also many stressors which can be triggered their impulsivity behavior. Consultation-liaison psychiatry can be conducted and need to be referred if the clinician found about emergency psychiatry evidence. Keywords: self-harm, pregnant, personality.